THE POSSIBLE PATHWAYS OF ANTI-DEPRESSANT ACTIVITY OF NARINGENIN IN ALBINO MICE USING FORCED SWIM TEST MODEL OF DEPRESSION - RUPASRI DUTT-ROY; KAYALVIZHI E; MANIKANDAN B; DAMEL LAKSHMI; CHANDRASEKHAR M (International Journal of Pharma and Bio Sciences, 2015)
Aim To evaluate the possible pathways of the anti-depressant activity of naringenin (5,7-dihydroxy-2-(4-hydroxyphenyl)chroman-4-one) in albino mice using the forced swimming test model. Material and methodsThe mechanism of action involved in the anti-depressant activity of naringenin in various doses (20mg/kg &50mg/kg,p.o.) was investigated by observing the effect of naringenin after pre-treatment with fluoxietine prazosin and haloperidol. para-chlorophenylalanine (p-CPA) was also used as a serotonin synthesis inhibitor .Results The results of forced swim test of naringenin significantly attenuated the duration of immobility induced by fluoxietine(15mg/kg/i.p. selective serotonin reuptake inhibitor) ,Haloperidol (0.2mg/ kg, i.p., a classical D2-like dopamine receptor antagonist) and, Prazosin (1mg/kg, i.p., an α-1-adrenoceptor antagonist) and p-chlorophenylalanine (100 mg/kg, i. p, × 3 days; an inhibitor of serotonin synthesis) .Conclusion It can be concluded that naringenin possess potential antidepressant activity (through dopaminergic, noradrenergic and serotonergic mechanisms) and has therapeutic potential in the treatment of CNS disorders